Seeing Further Than Your Nose. (May 2013) - van Tonder, Gert; Zavagno, Daniele; Sakurai, Kenzo; Ono, Hiroshi
Among monocular depth cues, ocular parallax (first described formally by Brewster in 1844) remains mostly unknown, its role in perception still not investigated scientifically. Given that every single eye movement induces ocular parallax, it is a potentially useful depth cue. This paper is an attempt to revive interest in the topic. As a monocular depth cue, ocular parallax naturally leads us to consider its benefit for a monocularly enucleated individual. Throughout history, numerous illustrious personalities coped with this fate in various ways. Here, we consider some historical insights into the visual life of the erstwhile duke of Urbino, Federico da Montefeltro (1422–1482), warlord and patron to the painter Piero della Francesca, and the Japanese warlord, Masamune Date (1567–636), a vocal patron of exploration and the arts.